Cuidado em saúde mental: a escuta de pacientes egressos de um Hospital Dia. - Ferreira, Maria Solange de Castro; Pereira, Maria Alice Ornellas (FapUNIFESP (SciELO), 2012)
This is a qualitative study aiming at understanding how patients discharged from a Mental Health Day Hospital view the service, at learning whether such service contributed to changes in their lives and at whether those individuals continued treatment. Semi-structured interviews and documental research were used for nine patients who had completed treatment at the service in 2008. Thematic analysis was adopted for organization of the data obtained, which were analyzed according to the Psychosocial Rehabilitation framework. It emphasizes the importance of looking for the various subjective aspects of human existence, requiring from services and professionals the establishment of a caring relationship that enables the reconstruction of trajectories interrupted by the onset of the disease, through actions that consider the integrality and intersectionality.
Mental health care: listening to patients discharged from a day hospital
Keywords: adult; day care; female; hospital discharge; human; male; mental disease; mental health service; middle aged; patient care; patient satisfaction; Adult; Continuity of Patient Care; Day Care; Female; Humans; Male; Mental Disorders; Mental Health Services; Middle Aged; Patient Discharge; Patient Satisfaction; Young Adult